Uzlah Dalam Tradisi Islam : Solusi Untuk Merevitalisasi Moral Masyarakat Modern - Kurniadi Ramadhan (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2024)
This article discusses the concept of uzlah in Islamic tradition and examines its potential as a solution for revitalizing the moral fabric of modern society. Uzlah, which means seclusion from the crowd to focus on worship and spiritual reflection, has long been practiced by Sufis and religious figures in Islam. In the modern context, characterized by materialism, technological advancement, and social complexity, uzlah offers a relevant approach to addressing emerging moral challenges.The research identifies various moral challenges faced by modern society, such as the disintegration of knowledge, the misuse of technology, and the fragmentation of personality. Through the practice of uzlah, individuals can rediscover spiritual and ethical values that have been marginalized, and enhance their moral and spiritual quality. Uzlah also helps avoid reprehensible acts like gossip, ostentation, slander, and hostility, promoting a more harmonious and respectful coexistence.By integrating religious teachings and scientific knowledge, this article asserts that uzlah is crucial not only for individual well-being but also for building a morally upright, moderate, and faithful society. The article concludes that uzlah is an effective solution that can be applied in modern life to revitalize the moral and spiritual aspects of society.